Constituents of essential oil from the stem of Schisandra perulata Gagnep. collected in Bat Xat district, Lao Cai province - Thanh, Bui Van; Ngoc Anh, Luu Dam; Huong, Bui Van; Hai, Nguyen Thi (Academia Journal of Biology, 2013)
The essential oil extrated from the stem of Schisandra perulata Gagnep. was prepared by steam distillation of fresh materials in a glass for 3h. The essential oil yields was 0.31% from the stem (in absolute dry material). The essential oil from the stem of Schisandra perulata Gagnep. analyzed by GC/MS consists of 45 constituents identified accounting more than 95.21% of the oil. The major components of the essential oil from the stem of Schisandra perulata Gagnep. are: zingiberene (14.77%), cadinene <d> (12.21%), santalene (9.60%), muurolol <epia> (8.20%), Cadinene <g> (6.49%), curcumene <ar> (5.07%), cubenol <1epi> (4.28%), copaene (4.02%) and all rest components with a content from 0.1 to 3.91%.